Step
*
1
of Lemma
assert-strong-regular-upto
1. a : ℕ
2. b : ℕ
3. n : ℕ
4. f : ℕ+ ⟶ ℤ
5. ↑strong-regular-upto(a;b;n;f)
6. i : ℕ+n + 1
7. j : ℕ+n + 1
⊢ (a * |(i * (f j)) - j * (f i)|) ≤ (b * (i + j))
BY
{ (Unfold `strong-regular-upto` -3
   THEN (RWW "assert-bdd-all" (-3) THENA Auto)
   THEN (InstHyp [⌜i - 1⌝;⌜j - 1⌝] (-3)⋅ THENA Auto)) }
1
1. a : ℕ
2. b : ℕ
3. n : ℕ
4. f : ℕ+ ⟶ ℤ
5. ∀i,j:ℕn.  (↑a * |((i + 1) * (f (j + 1))) - (j + 1) * (f (i + 1))| ≤z b * ((i + 1) + j + 1))
6. i : ℕ+n + 1
7. j : ℕ+n + 1
8. ↑a * |(((i - 1) + 1) * (f ((j - 1) + 1))) - ((j - 1) + 1) * (f ((i - 1) + 1))| ≤z b * (((i - 1) + 1) + (j - 1) + 1)
⊢ (a * |(i * (f j)) - j * (f i)|) ≤ (b * (i + j))
Latex:
Latex:
1.  a  :  \mBbbN{}
2.  b  :  \mBbbN{}
3.  n  :  \mBbbN{}
4.  f  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
5.  \muparrow{}strong-regular-upto(a;b;n;f)
6.  i  :  \mBbbN{}\msupplus{}n  +  1
7.  j  :  \mBbbN{}\msupplus{}n  +  1
\mvdash{}  (a  *  |(i  *  (f  j))  -  j  *  (f  i)|)  \mleq{}  (b  *  (i  +  j))
By
Latex:
(Unfold  `strong-regular-upto`  -3
  THEN  (RWW  "assert-bdd-all"  (-3)  THENA  Auto)
  THEN  (InstHyp  [\mkleeneopen{}i  -  1\mkleeneclose{};\mkleeneopen{}j  -  1\mkleeneclose{}]  (-3)\mcdot{}  THENA  Auto))
Home
Index